Adiponectin and 8-epi-PGF2α as intermediate influencing factors in weight reduction after legume consumption: a 12-week randomised controlled trial. Issue 2 (28th January 2022) - Han, Youngmin; Kim, A Ram; Lee, Jong Ho; Kim, Minjoo
Abstract : Abstract: Legumes are rich sources of essential nutrients, and their potential health benefits were reported in many studies. Several studies showed a positive effect of legumes on obesity, but randomised clinical trials are limited in the Korean population. The present intervention study investigated the impact of legumes on body weight in obese Korean subjects. A total of 400 participants (BMI ≥ 25 kg/m 2 ) were randomised into two groups. The legume-enriched diet (LD) group replaced one-third of their refined rice consumption with legumes three times per day as a carbohydrate source. In contrast, the usual diet (UD) group consumed their UD. The mean weight loss at 12 weeks was 2·87 (sem 0·21) kg and 0·17 (sem 0·11) kg in the LD and UD, respectively, which was significantly different between the groups ( P < 0·001). HDL-cholesterol and adiponectin levels were increased, and levels of glucose, insulin, TAG, and 8-epi-PGF2α and the homoeostasis model assessment of insulin resistance (IR) index value decreased at 12 weeks compared with baseline in the LD. The consumption of legumes may accelerate weight loss accompanied by regulation of adiponectin and 8-epi-PGF2α in obese subjects. In particular, legumes seemed to induce significant changes in BMI by increasing adiponectin in females. Additionally, increases in plasma adiponectin due to greater substantial weight loss may be related to the improvement in IR.